The Influence of Self-Service Experiences on Customer Satisfaction - Norashikin, Jalani; Azizan, Azit; Wan Khairul Anuar, Wan Abd Manan; Mazita, Mokhtar (Penerbit Universiti Malaysia Pahang, 2023)
Successful companies consistently provide higher levels of satisfaction to their customers. This study is to determine the impact of self-service experiences on customer satisfaction. For the purpose of the study, 120 McDonald's customers were selected for a survey. The results showed that being technologically ready positively and substantially affects customer satisfaction through the medium of Customer Trust. Self-service can be more efficient and successful, and customers can be more satisfied if the necessary technology is in place. Self-service experience quality and client satisfaction are impacted by trust and perceived value. This research contributes to understanding what it takes to keep repeat customers happy and returning for more business.